Practical patient dosimetry for partial rotation cone beam CT - Podnieks, E C (The British Institute of Radiology., 2012)
OBJECTIVES: This work investigates the validity of estimating effective dose for cone beam CT (CBCT) exposures from the weighted CT dose index (CTDIW) and irradiated length. METHODS: Measurements were made within cylindrical poly(methyl methacrylate) (PMMA) phantoms measuring 14 cm and 28 cm in length and 32 cm in diameter for the 200° DynaCT acquisition on the Siemens Artis zee fluoroscopy unit (Siemens Medical Solutions, Erlangen, Germany). An interpolated average dose was calculated to account for the partial rotation. Organ and effective doses were estimated by modelling projections in the Monte Carlo software programme PCXMC (STUK, Helsinki, Finland). RESULTS: The CTDIW was found to closely approximate the interpolated average dose if the positions of the measured doses reflected the X-ray beam rotation. The average dose was found to increase by 8% when the phantom length was increased from 14 to 28 cm. Using the interpolated average dose and the irradiated length for effective dose calculations gave similar values to PCXMC when a double-length (28-cm) CT dose index phantom was irradiated. Simplifying the estimation of effective dose with PCXMC by modelling just 4 projections around the abdomen gave effective doses that were only 7% different to those given when 41 projections were modelled. Calculated doses to key organs within the beam varied by as much as 27%. CONCLUSION: Estimating effective dose from the CTDIW and the irradiated length is sufficiently accurate for CBCT if the chamber positions are considered carefully. A conversion factor can be used only if a single CT dose index phantom is available. The estimation of organ doses requires a large number of modelled projections in PCXMC.